2005
DOI: 10.1002/cne.20701
|View full text |Cite
|
Sign up to set email alerts
|

Identification of roughskin newt medullary vasotocin target neurons with a fluorescent vasotocin conjugate

Abstract: Arginine8 vasotocin (AVT), a neurohypophyseal peptide in nonmammalian vertebrates, plays a key role in the regulation of social behaviors related to reproduction. In male roughskin newts (Taricha granulosa), AVT is an important facilitator of several reproductive behaviors, including courtship clasping of females. Although AVT is known to act in certain brain regions and AVT receptors have been localized to some extent, specific target neurons for this peptide have not been identified in any species. Internali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…In our study, we have histochemically confirmed the presence of V1a-type receptor in these regions of the brain of C. pyrrhogaster. Medullary AVT target neurons, particularly those in the medial reticular formation and nuclei of cranial nerves, have recently been visualized by means of Oregongreen-conjugated AVT (Lewis et al 2004(Lewis et al , 2005. These neurons coincide with those exhibiting V1a-type-receptorlike immunoreactivity in the brain of C. pyrrhogaster.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we have histochemically confirmed the presence of V1a-type receptor in these regions of the brain of C. pyrrhogaster. Medullary AVT target neurons, particularly those in the medial reticular formation and nuclei of cranial nerves, have recently been visualized by means of Oregongreen-conjugated AVT (Lewis et al 2004(Lewis et al , 2005. These neurons coincide with those exhibiting V1a-type-receptorlike immunoreactivity in the brain of C. pyrrhogaster.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical nomenclature as given in Table 2 is based on the studies of Smeets (1992a, 1992b), Lowry et al (1997), Lewis et al (2005), and Hollis et al (2006).…”
Section: Anatomical Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…In one study, fluorescently labeled AVT was administered directly to the brain of newt and specific cell populations in the reticular formation of the hind brain were labeled and identified as areas of AVT action (Lewis et al, 2005). Similarly, only one study in fish has reported identification of AVT binding sites in the pituitary and several generalized brain regions in the seabass, Dicentrarchus labrax (Moons et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…There are VT terminals (Lowry et al 1997) and receptors (Boyd & Moore 1991;Lewis et al 2005) in the newt medulla, although the source of those projections and the circuits through which olfactory stimuli activate them have not yet been identified. Additionally, although we did not characterize individual neuronal responses as did Rose et al (1995), and thus cannot say whether individual neurons are firing more or previously unresponsive neurons are being recruited in response to FSW, our present results are consistent with what they observed when exogenous VT was applied to the medulla, which was that neuronal responses to somatosensory stimuli typically increased.…”
Section: Discussionmentioning
confidence: 99%